Bamboo-derived wood vinegar improves the growth and yield of corn under varying application levels - Torres, Mary Rose Giban; Macasait Jr, Dionesio Requioma; Arribado, Arwin Orcales; Pedrosa, Sonia Laurino (International Journal of Sustainable Agricultural Research, 2025)
Corn is a vital staple crop in the Philippines, but its production heavily depends on chemical fertilizers that can cause soil degradation and nutrient loss. This study aimed to assess the response of corn to varying levels of bamboo-derived wood vinegar on growth performance. The treatments included T0 (control) with 0 mL, T1 with 10 mL, T2 with 20 mL, and T3 with 30 mL of wood vinegar (WV) per liter of water, while T4 received a commercial fertilizer application. Growth parameters such as plant height, cob diameter, and days to silking were measured. Results showed significant differences in plant height (P=0.040) at the fourth week, cob diameter (P=0.021), and days to silking (P=0.019), indicating that wood vinegar enhanced specific growth attributes. However, no significant effects were observed on the number of leaves, days to tassel, ear length, 1000-kernel weight, and biomass percentage. These findings suggest that bamboo-derived wood vinegar can serve as a supplementary growth enhancer, offering a potential eco-friendly alternative to synthetic fertilizers, and it can positively impact specific corn growth parameters. Further studies are recommended to explore other sources of wood vinegar and application methods to maximize its agricultural benefits.